A Comparative Study on the Radiation Preservation of Marine (Seer fish) as well as Fresh Water Fish (Cat fish) - P.S., Sree Rekha; K.M., Nishamol; M.D., Alur; D.R., Bongirwar (Fishery Technology, 2025)
Seer, a marine fish and cat fish, a fresh water fish, were compared for their amenability to radiation preservation during storage at 2-30C employing sensory, bacteriological and biochemical parameters. Although both the fish varieties exhibited a two-fold extension in shelf life by radiation treatment at 1-3 kGy over controls, the biochemical parameters tested (TMAN and TVBN) failed to monitor the quality of fresh water fish (cat fish). On the other hand, with respect to marine fish (seer), biochemical and microbiological quality correlated well with sensory evaluation data.